Tilføjelse til “Grundtvig og censuren” i Grundtvig-Studier 2007 - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 2008)
Tilføjelse til “ Grundtvig og censuren ” i Grundtvig-Studier 2007[Supplement to “ Grundtvig and censorship ” in Grundtvig-Studier 2007]By Flemming Lundgreen-Nielsen The supplement to “ Grundtvig and censorship” in Grundtvig-Studier 2007 (44-90; 281) presents the discovery that Grundtvig’s idea from 1831 about an age limit for young writers may have been influenced by Ludvig Holberg’s description of academic restrictions in the fictitious state of Potu in his Latin novel Niels Kliim, 1741, chapter 8, recycled in his essay Epistle No. 395, 1750. A polite protest against Holberg by C. B. Tullin was published posthumously in 1773, emphasising the freedom of printing and the advantage of competition among writers. Grundtvig regrets his strange elitist conception already in 1836, but the point may be that he has in fact been inspired to some of his discussions on education and freedom of speech and printing by leading writers from the Danish Enlightenment of the eighteenth century in spite of his often proclaimed general dissociation from that period.